If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -4) = 3(3x + 8) Reorder the terms: 6(-4 + 2x) = 3(3x + 8) (-4 * 6 + 2x * 6) = 3(3x + 8) (-24 + 12x) = 3(3x + 8) Reorder the terms: -24 + 12x = 3(8 + 3x) -24 + 12x = (8 * 3 + 3x * 3) -24 + 12x = (24 + 9x) Solving -24 + 12x = 24 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -24 + 12x + -9x = 24 + 9x + -9x Combine like terms: 12x + -9x = 3x -24 + 3x = 24 + 9x + -9x Combine like terms: 9x + -9x = 0 -24 + 3x = 24 + 0 -24 + 3x = 24 Add '24' to each side of the equation. -24 + 24 + 3x = 24 + 24 Combine like terms: -24 + 24 = 0 0 + 3x = 24 + 24 3x = 24 + 24 Combine like terms: 24 + 24 = 48 3x = 48 Divide each side by '3'. x = 16 Simplifying x = 16
| 23+18x=21+14x | | 5m-9=-3m+7 | | 8x+5=-17 | | 3y=3x-1 | | x-40=-4x+5 | | -5.3=0.8+2g | | 8d+50=3d | | x^2y^2+196= | | 2log(x)-log(3)=1 | | 3x-24+2x+1=180 | | 8+5y=-17 | | g+9=15 | | 36s^2-4t^2= | | 4c^2-12ct+9t^2= | | x-40=4x+5 | | 6(m+3)-2m=38 | | r-4=8 | | -5/3x=-15 | | 1-m^6= | | 4x=(3x+40) | | 6+4a-1+6a= | | 110-32= | | 6.21y+3-4.5y+1.45=3.5y | | 3(-1+3y)+3=3y | | -13x=x^2 | | 1+s=10 | | 4(n-3)+6=4n-3 | | 50+2x+2x+20=180 | | 8+n=17 | | 3+d=17 | | 8(x-4)=75 | | 7(c-12)=-2 |